Optimising laboratory monitoring of chronic conditions in primary care: a quality improvement framework - Alex J Walker; Richard Croker; Jessica Watson; Andy Brogan; Darunee Whiting; Tom Lewis (BMJ Open Quality)
Monitoring of chronic conditions accounts for a significant proportion of blood testing in UK primary care; not all of this is based on evidence or guidelines. National benchmarking shows significant variation in testing rates for common blood tests. This project set out to standardise the blood tests used for monitoring of chronic conditions in primary care across North Devon, and to measure and reduce the harms of unwarranted testing. Chronic disease test groups were developed in line with current guidelines and implemented using one-click electronic test ordering systems. The main difference from previous general practitioner practice algorithms was removing the requirement for full blood count and liver function test monitoring for many conditions. Baseline harms of testing were measured and included significant costs, workload and patient anxiety. By defining the scale of the problem, we were able to leverage change across several cycles of quality improvement, using a pathology optimisation forum for peer-led improvement, and developing a framework focusing on what matters to patients. Overall primary care testing rates in North Devon fell by 14% for full blood count testing and 22% for liver function tests, but without a reduction in the number of tests showing possible significant pathology. We estimate that this has reduced testing costs by £200 000 across a population of around 180 000 people and has reduced downstream referral costs by a similar amount. Introduction of simple chronic disease test groups into primary care electronic ordering systems, when used alongside engagement with clinicians, leads to both quality improvement and reduction in system costs.